Outdoor therapies : introduction to practices, possibilities, and critical perspectives - Harper, Nevin J.; Dobud, Will W. (New York, NY : Routledge, 2021)
Drawing on the leading voices of international researchers and practitioners, Outdoor Therapies provides readers with an overview of practices for the helping professions. Sharing outdoor approaches ranging from garden therapy to wilderness therapy and from equine-assisted therapy to surf therapy, Harper and Dobud have drawn common threads from therapeutic practices that integrate connection with nature and experiential activity to redefine the "person-in-environment" approach to human health and well-being. Readers will learn about the benefits and advantages of helping clients get the treatment, service, and care they need outside of conventional, office-based therapies. Providing readers with a range of approaches that can be utilized across a variety of practice settings and populations, this book is essential reading for students, practitioners, theorists, and researchers in counseling, social work, youth work, occupational therapy, and psychology.
OCLC-licensed vendor bibliographic record.
Keywords: Adventure therapy; Nature -- Therapeutic use; Ecopsychiatry; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Psychotherapy / Counseling